Redefining the collateral system between the superior mesenteric artery and inferior mesenteric artery: a novel classification. (24th January 2021) - Kuzu, Mehmet Ayhan; Güner, Mehmet Ali; Kocaay, Akın Fırat; İsmail, Erkin and Arslan, Murat Nihat and Tekdemir, İbrahim and Açar, Halil İbrahim
Abstract: Aim: The aim of this study was to evaluate the arterial collateral vasculature between the superior mesenteric artery and the inferior mesenteric artery (IMA) from a surgical perspective. Method: A total of 107 fresh adult cadavers (94 male) were studied with emphasis on the vascular anatomy of the left colon. Dissections were carried out mimicking the anterior resection technique. The vasculature of the left mesocolon and the collaterals between the superior mesenteric artery and the IMA with respect to their relationship to the inferior mesenteric vein (IMV) were assessed and classified. Collaterals were classified into three different groups: marginal anastomoses (via the marginal = pericolic artery), intermediate mesocolic anastomoses (parallel to the marginal artery but neither adjacent to the IMV nor close to the duodenum) and central mesocolic anastomoses (next to the IMV at the level of the duodenojejunal junction and the lower border of the pancreas). Results: All patients had a marginal anastomosis. However, the marginal anastomosis, as the only anastomosis between the superior and inferior mesenteric arteries at the splenic flexure, was observed in 41 cases (38%). In addition to the marginal artery, intermediate mesocolic anastomoses were found in 49 (46%) and a central mesocolic anastomosis was observed in 17 (16%) of the 107 cases in the splenic flexure mesocolon. It is in this latter variant that collateral vessels can be compromised during ligation/transection of the IMV. Conclusion: This new classification can contribute to a precise mesocolic dissection technique and splenic flexure mobilization and help prevent ischaemic damage to the descending colon.